MicroRNA-494-3p inhibits formation of fast oxidative muscle fibres by targeting E1A-binding protein p300 in human-induced pluripotent stem cells - Hirotaka Iwasaki (Nature Portfolio, 2021)
Abstract MYOD-induced microRNA-494-3p expression inhibits fast oxidative myotube formation by downregulating myosin heavy chain 2 (MYH2) in human induced pluripotent stem cells (hiPSCs) during skeletal myogenesis. However, the molecular mechanisms regulating MYH2 expression via miR-494-3p remain unknown. Here, using bioinformatic analyses, we show that miR-494-3p potentially targets the transcript of the E1A-binding protein p300 at its 3′-untranslated region (UTR). Myogenesis in hiPSCs with the Tet/ON-myogenic differentiation 1 (MYOD1) gene (MyoD-hiPSCs) was induced by culturing them in doxycycline-supplemented differentiation medium for 7 days. p300 protein expression decreased after transient induction of miR-494-3p during myogenesis. miR-494-3p mimics decreased the levels of p300 and its downstream targets MYOD and MYH2 and myotube formation efficiency. p300 knockdown decreased myotube formation efficiency, MYH2 expression, and basal oxygen consumption rate. The binding of miR-494-3p to the wild type p300 3′-UTR, but not the mutated site, was confirmed using luciferase assay. Overexpression of p300 rescued the miR-494-3p mimic-induced phenotype in MyoD-hiPSCs. Moreover, miR-494-3p mimic reduced the levels of p300, MYOD, and MYH2 in skeletal muscles in mice. Thus, miR-494-3p might modulate MYH2 expression and fast oxidative myotube formation by directly regulating p300 levels during skeletal myogenesis in MyoD-hiPSCs and murine skeletal muscle tissues.